Comparison of the acute effects of static and dynamic stretching exercises on the balance performance of Turkish wrestlers - Durukan, E.; Aydin, G.; Goktepe, M.; Cicek, G.; Guder, F.; Isik, O. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The importance of dynamic and static stretching exercises on motoric abilities before an athletic performance is well known. However, there is limited information about their effects on balance performance. For this reason, this study aimed to investigate the acute effects of static and dynamic stretching exercises on wrestlers` balance performance and compare wrestlers` balance levels according to their wrestling styles.